Quality of Tax Administration : How Relevant Is Country Size? - Amin, Mohammad (2012)
Repeated attempts at uncovering the relevance of country size for various economic factors have produced discouraging results. The present paper sheds new light on the relevance of country size using micro or firm-level data on firms' experience with the quality of tax administration, an important but neglected element of the business climate. The analysis finds that the quality of tax administration is significantly better for small compared with large countries. The instrumental variables regression method confirms that this finding is robust to various endogeneity concerns. The paper also finds some evidence that the country size and tax administration relationship is non-linear, and much stronger for small than large countries. Implications of these findings for the broader literature on country size are discussed.